Soccer shocker - Krulik, Nancy E.; Burwasser, Amanda Elizabeth (Krulik, Nancy E. Project droid, 2016)
"When Java joins Logan's soccer team, becoming the best player (as only a robot can), Logan must learn that the team comes first"--